FORMSpoT: Revealing fine-scale forest disturbances from nation-wide 1.5 m forest canopy height time series - Martin Schwartz; Fajwel Fogel; Nikola Besic; Damien Robert; Louis Geist; Jean-Pierre Renaud; Jean-Matthieu Monnet; Clemens Mosig; Cédric Vega; Alexandre d’Aspremont; Loic Landrieu; Philippe Ciais (Remote Sensing of Environment, 2026)

Fish vulnerability to overfishing based on meta-analytical trait estimates: how alternative productivity assumptions influence risk assessment under a novel approach - Alexandre R. dos Santos; Marcelo F. Nóbrega; Maurício C. Robert; Jorge E. Lins Oliveira; Rosangela P. T. Lessa; Jason M. Cope (Reviews in Fish Biology and Fisheries, 2026)

Modelling primary production: multitude of theories, or multitude of languages? - Jozef Skákala; Shubha Sathyendranath; Yuri Artioli; Deep S. Banerjee; Heather Bouman; Robert J. W. Brewin; Momme Butenschön; Stefano Ciavatta; Stephanie Dutkiewicz; Yanna Fidai; David Ford; Grinson George; et al. (Ocean Science, 2026)
Marine primary production, converting approximately 50 Gt of inorganic carbon into organic carbon per year, is an important component of the global carbon cycle, and a major determinant of past, present and future climate. Large-scale, long-term estimates of marine primary production rely primarily on two types of models: satellite-based models that make extensive use of remote-sensing data, and ecosystem models providing numerical simulation of ecological processes embedded in general ocean circulation models. Intercomparison exercises of model outputs (both within and across the two model types) have consistently revealed high discrepancies between estimated global ocean primary production, including divergent magnitudes and even opposite trends. Model-observation comparisons are also complex, because paucity of data, differences in measurement techniques, and evolving methodologies could all lead to difficulties with the interpretation of results. These uncertainties limit the applications of primary production models (both satellite-based and ecosystem), especially in the climate context, where an important question is whether climate change will drive significant future changes in regional or global primary production. Both satellite-based and ecosystem models rely on a range of fixed model parameters, whose values need to be carefully estimated and tested. In this paper, we suggest that such model parameters represent an underappreciated but important source of inter-model differences. With the proliferation of both satellite and in situ observations of relevant variables at global scales, and the availability of powerful statistical tools such as data assimilation and machine learning, we argue that time is right to systematically examine model parameters, gaining both better insights into parameter values and how those values might vary in space and time. We argue that such spatio-temporal parameter variability can be theoretically justified for ecosystem models with complexity similar to those commonly used within Earth System Models (ESMs) in climate studies. The spatially and temporally varying parameter values could serve to unify models that are structurally different. An important aspect of this unification could be the ability to infer the spatio-temporal variability of parameters in the less complex models from the emergent behaviour of the more complex ones. This could include ecosystem model simulations of nutrients, temperature, phytoplankton classes, or vertical distributions informing satellite-based models. We conclude that better understanding of model parameter roles and integration (or inter-calibration) of different types of models could reduce discrepancies among the primary production models and improve the reliability of marine primary production projections.

Distribution and taxonomic composition of leptocephali and hydrographic structure from New Zealand to the South Equatorial Current - Michael J. Miller; Shun Watanabe; Robert Schabetsberger; Nioka Behan-Kitto; Grace F. Cawley; Niamh Smith; Alisha M. Gill; Alexandre Che-Pelicier; Juliet E. Saul; Abigail Sim; Therese C. Miller; Sajini Dissanayake; et al. (Regional Studies in Marine Science, 2026)

Effects of Channel Characteristics on Wastewater Chemical Transformation in Rivers - Robert A. Newbould; D. Mark Powell; Juliet Hodges; Alexandre Teixeira; Michael J. Whelan (Water, Air, & Soil Pollution, 2026)
Microbially-mediated transformations are important for removing wastewater chemicals in rivers. In-stream degradation rates are likely to be affected by channel morphology and size because these factors determine the extent of chemical contact between the water column and the microbial community in fixed biofilms, where most microbially-mediated processes are expected to take place. We hypothesize that transformation rate constants are inversely proportional to hydraulic radius ( R : the ratio of channel cross-sectional area to wetted perimeter). Microbial transformations are also predicted to be controlled systematically by bed sediment characteristics. This will be a function of sediment surface area per unit volume (for biofilm colonisation) and hyporheic exchange. Here, we test the above hypotheses in controlled 14-day laboratory experiments, by monitoring nitrification and biodegradation in stirred tanks with three different water depths and three different sediment sizes (sand, gravel and cobbles). Transformation rate constants were inversely proportional to depth, supporting the notion that channel morphology represents a significant system-specific control. Rate constants for nitrification were highest in the gravel treatments and lowest in sand. This suggests that intermediate grain sizes simultaneously allow good biofilm colonisation and solute exchange between sediment and the water column. There was, however, little difference in biodegradation rate constants between different sediment sizes. This study highlights the need to consider geomorphology in models of chemical exposure.

Peripheral microRNA signature in genetic frontotemporal dementia—findings from the GENFI initiative - Chiara Fenoglio; Maria Serpente; Marina Arcaro; Tiziana Carandini; Luca Sacchi; Manuela Pintus; Vittoria Borracci; Giulia Giudici; Marta Rigoni; Paola Muti; Laura Ghezzi; Arabella Bouzigues; et al. (GeroScience, 2026)
Frontotemporal dementia (FTD) is a neurodegenerative disease characterized by significant clinical and genetic heterogeneity, with approximately 40% of cases linked to hereditary genetic mutations, including MAPT , GRN , and C9ORF72 . Recently, microRNAs (miRNAs) have emerged as key regulators of cellular processes related to neurodegeneration and as potential biomarkers for FTD. However, their relevance in presymptomatic stages remains poorly understood. We conducted a miRNA expression analysis using TaqMan OpenArray® panels on blood samples collected from 171 individuals, including symptomatic mutation carriers (SMC), presymptomatic carriers (PMC), and healthy non-carriers (NC). Dysregulated miRNAs were validated and bioinformatic tools were used to identify potential associated molecular pathways. In C9ORF72 , miR-20b-5p and miR-223-5p were significantly upregulated in SMC (fold regulation over NC: 2.418 p = 0.0336 and 7.829 p < 0.0264 respectively) and PMC (5.518, p < 0.0001 and 3.941, p < 0.0001 respectively). In GRN mutation carriers, miR-28-3p was altered in both SMC and PMC (fold regulation over NC: 1.484 p < 0.050 and 3.287, p < 0.050). In MAPT mutation carriers, miR-28-5p, miR-192-3p, miR-25-3p, and miR-532-3p were altered only in SMC (fold regulation over NC: 1.496 p < 0.050, 1.911 p = 0.006, 1.468 p < 0.05, and 0.728 p < 0.05). Bioinformatic analysis revealed enrichment of pathways related to neurodegeneration and synapse impairment. These results suggest that miRNA expression levels are deregulated in mutated SMC, in C9ORF72 and GRN PMC. Notably, miR-20b-5p, miR-223-5p, and miR-28-3p were increased in preclinical stages of the disease, supporting their role as early biomarkers for C9ORF72 -FTD and GRN -FTD. Conversely, alterations in MAPT carriers appeared only in symptomatic stages, suggesting a different involvement in disease progression.

Ecological and economic assessments of native vertebrate pest control in France - Frédéric Jiguet; Aïssa Morin; Héloïse Courtines; Alexandre Robert; Benoit Fontaine; Harold Levrel; Karine Princé (Biological Conservation, 2026)

Advances in plant spatial multi-omics data analysis - Jie Yao; Alexandre P. Marand; Yinqi Bai; Robert J. Schmitz; Longjiang Fan (Trends in Plant Science, 2026)

The plant ontology of cell types - Hongyu Chen; Pu Liang; Xiaolin Lu; Shuai Jiang; Jingjing Jin; Jiaqi Cai; Yaqian Lu; Dihuai Zheng; Jie Yao; Qinjie Chu; Huixia Shou; Chengxin Fu; et al. (Molecular Plant, 2026)

Neurotoxicity and teratogenicity induced by carbendazim and ametryn in zebrafish: Implications for environmental and biological health - Júlia Robert Teixeira; Livia Alves de Macedo Tavares; Ariana Pereira da Silva; João Vitor de Macedo-Sampaio; Hugo Alexandre de Oliveira Rocha; Katia Castanho Scortecci; Bruno Fiorelini Pereira; Ana Carolina Luchiari (Environmental Toxicology and Pharmacology, 2026)

WABAD : A world annotated bird acoustic dataset for passive acoustic monitoring - Cristian Pérez‐Granados; Jon Morant; Kevin F. A. Darras; Oscar H. Marín‐Gómez; Irene Mendoza; Miguel A. Muñoz‐Mohedano; Eduardo Santamaría‐García; Giulia Bastianelli; Alba Márquez‐Rodríguez; Michał Budka; Gerard Bota; José M. De la Peña‐Rubio; et al. (Ecology, 2026)
Under the current global biodiversity crisis, there is a need for automated and noninvasive monitoring techniques that can gather large amounts of data cost‐effectively at various ecological scales, from local to large spatial scales. These data can then be analyzed to inform stakeholders and decision‐makers. One such technique is passive acoustic monitoring, which is commonly coupled with automatic identification of animal species based on their sound. Automated sound analyses usually require the training of sound detection and identification algorithms. These algorithms are based on annotated acoustic datasets which mark the occurrence of sounds of species inside sound recordings. However, compiling large annotated acoustic datasets is time‐consuming and requires experts, and therefore, they normally cover reduced spatial, temporal, and taxonomic scales. This data paper presents WABAD, the World Annotated Bird Acoustic Dataset for passive acoustic monitoring. WABAD is designed to provide the public, the research community, and conservation managers with a novel and globally representative annotated acoustic dataset. This database includes 5047 min of audio files annotated to species‐level by local experts with the start and end time and the upper and lower frequencies of each identified bird vocalization in the recordings. The database has a wide taxonomic and spatial coverage, including information on 91,931 vocalizations from 1192 bird species recorded at 72 recording sites in 29 recording locations (mainly countries) and distributed across 13 biomes. WABAD can be used, for example, for developing and/or validating automatic species detection algorithms, answering ecological questions, such as assessing geographical variations on bird vocalizations, or comparing acoustic diversity indices with species‐based diversity indices. The dataset is published under a Creative Commons Attribution 4.0 International license that permits redistribution and reuse on the condition that the original work is properly credited.

Clinical spectrum of ICU-acquired invasive pulmonary aspergillosis according to SARS-CoV2 infection: a multicenter prospective cohort study - Florian Reizine; Mattéo Mauget; Nicolas Massart; Yannick Fedun; Anaïs Machut; Charles-Hervé Vacheron; Anne Savey; Arnaud Friggeri; Alain Lepape; Melissa Abbes; Abdelkrim Abdelmalek; Francoise Adema; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Longitudinal effects of cerebrovascular reactivity and cerebral pulsatility in cognitively intact older adults with APOE4: links with cognition - Zacharie Potvin-Jutras; Pierre-Luc Tremblay; Hanieh Mohammadi; Sylvia Villeneuve; R. Nathan Spreng; Claudine J. Gauthier; Sylvia Villeneuve; Judes Poirier; John C.S. Breitner; Jennifer Tremblay-Mercier; Jordana Remz; Jean-Michel Raoult; et al. (GeroScience, 2025)

Forest fires in Caatinga: Risk modeling and priority areas for prevention - Mariana de Aquino Aragão; Nilton Cesar Fiedler; Alexandre Rosa dos Santos; Tais Rizzo Moreira; Antonio Henrique Cordeiro Ramalho; Robert Gomes; Patrícia Carneiro Souto; Telma Machado de Oliveira Peluzio; Jéferson Luiz Ferrari; Danilo Simões; Leonardo Duarte Biazatti; Fernanda Moura Fonseca Lucas (Perspectives in Plant Ecology, Evolution and Systematics, 2025)

Inbreeding Depression Across Multiple Life‐History Traits in a Long‐Lived Mammal - Léa Auclair; Cécile Vanpé; Guillaume Chapron; Pierre‐Yves Quenette; Alexandre Robert (Molecular Ecology, 2025)
Inbreeding depression is widely recognised as a near‐universal phenomenon of high conservation concern, particularly as wild populations continue to decline. However, most research to date has focused on early life stages, leaving later‐life effects comparatively understudied, especially for wild populations of long‐lived species. The Pyrenean brown bear ( Ursus arctos ), characterised by a small population, high levels of inbreeding and conflicts with human activities, embodies the conservation challenges faced by many large mammals. We analysed 27 years of monitoring data to quantify inbreeding depression across multiple life stages on survival, reproduction and dispersal. Our results reveal strong inbreeding depression effects, particularly in early life stages, including a reduction in litter size and in natal dispersal distance. In adults, more inbred mothers exhibit lower cub survival. The cumulative effect of inbreeding, as measured by lifetime breeding success, also shows a negative impact. These findings highlight the necessity of assessing inbreeding depression across the entire life cycle to accurately evaluate its threat to population dynamics and viability. Such comprehensive assessments will become increasingly essential for wild plant and animal populations constrained by habitat destruction, human–wildlife conflict and harvesting pressures.

Revealing Chronotypes Across Aquatic Species Using Acoustic Telemetry - Martina Martorell‐Barceló; David Abecasis; Mourad Akaarir; Alexandre Alonso‐Fernández; Robert Arlinghaus; Eneko Aspillaga; Margarida Barcelo‐Serra; Niels W. P. Brevé; Jan G. Davidsen; Antoni Gamundí; Amalia Grau; Bernat Hereu; et al. (Fish and Fisheries, 2025)
Acoustic telemetry offers valuable opportunities to investigate individual variability in circadian‐related and other behaviours and how environmental cues shape these patterns in wild fish populations. However, this potential has not yet been fully exploited. We conducted a meta‐analysis on 44 datasets from 34 distinct marine and freshwater species and different types of data (acoustic detections, depth, acceleration and positioning). Our aim was to explore the potential of acoustic telemetry in identifying chronotypes as consistent among‐individual differences in circadian‐related behaviours. First, we applied hidden semi‐Markov models to classify individual time series into active and rest states. Subsequently, we computed two classical circadian‐related behavioural traits: awakening time (as the activity onset) and rest onset (as the activity offset). Subsequently, we identified distinct phenotypes by decomposing behavioural variation into within‐ and among‐individual components based on repeatability scores. We found evidence of distinct chronotypes in 17 species, with average repeatability scores of 0.52 for awakening time and 0.43 for rest onset, revealing that chronotypes are common in aquatic species. Our findings highlight that both the data type, particularly acceleration sensors, and the number of detections are effective tools for exploring chronotypes. Our study proposes a novel approach to characterising daily activity patterns in aquatic species, predominantly in fishes, and provides guidelines for investigating chronotypes across diverse taxa. We emphasise the promise of biotelemetry and advanced statistical models for improving our understanding of the behaviour of aquatic species and highlight the value of synthesising across large data sets collected in networks of biotelemetryprojects.

Development and validation of a thermal desorption method based on Py-GC-HRMS using in-house reference materials to quantify a set of additives in polypropylene - Saïd Rekibi; Robert Heidrich; Anton Mordvinkin; Michel Laurentie; Guillaume Duflos; Thierry Grard; Alexandre Dehaut (Analytica Chimica Acta, 2025)

Humidity Control and Its Implications in the Storage of Apples and Pears: A Review - Robert K. Prange; A. Harrison Wright; Barbara J. Daniels-Lake; Daniel Alexandre Neuwald; Dirk Köpcke; Luiz Carlos Argenta (Applied Fruit Science, 2025)
At harvest, the water content of apples and pears is at its maximum, about 83–85% by mass. The rate of fruit water loss after harvest is a function of three factors: the fruit surface area, the epidermis water vapour permeance, and the difference in internal and external fruit water vapour pressure. However, the water vapour pressure difference is the only factor that can be controlled during storage, i.e. by altering the storage humidity. Curiously, most publications on apple and pear storage do not discuss storage humidity even though the postharvest quality of both depends largely upon it. Apples and pears can experience up to ~ 2% mass loss without loss of commercial value, but further mass loss creates visible shrivelling, and may also increase bitter pit, depending on the cultivar. The prevailing commercial advice has been to minimise mass loss by maximising the relative humidity at the chosen storage temperature. However, this advice should be re-evaluated, and humidity management protocols revised, from minimising mass loss to optimising mass loss. Growing evidence indicates that storage humidity affects the postharvest performance of apples and pears. A review of the literature over the last 100 years shows that some mass loss, achieved by lowering storage atmosphere humidity, can improve apple and pear quality by reducing non-bitter pit disorders, bruising, respiration, ethylene production and decay, especially if the mass loss occurs at the beginning of storage. The effects of mass loss on calcium-related disorders suggest that mass loss may affect postharvest calcium redistribution in the fruit. The fruit mass loss for refrigerated air and controlled atmosphere rooms can be estimated by collecting the defrost water from the refrigeration cooling coils and expressing this as a percentage of the initial total mass of fruit in the room. A ‘2-in-2’ guideline (up to 2% mass loss in the first 2 months) is proposed, but further research is needed to refine this guidance, especially for cultivars that may benefit from greater mass loss without increasing shrivelling or bitter pit.

Taxonomic and phylogenetic biases in translocated angiosperm plant species across European countries - Filipa Coutinho Soares; Maud Mouchet; Anne‐Christine Monnet; Nadline Kjelsberg; Alfredo García Fernández; Alexandre Robert; Jean‐Baptiste Mihoub; Bruno Colas; François Sarrazin (Conservation Biology, 2025)
Conservation translocations are a well‐known conservation tool used to reverse the effects of local population extinctions and restore ecosystems. Compared with mammals and birds, plants are underrepresented in translocation programs, and little is known about the potential taxonomic and phylogenetic biases of plant translocation efforts. We aimed to assess how translocated plant species may contribute to the conservation of phylogenetic diversity (PD) among European countries. Focusing on angiosperms across 4 European countries with well‐documented flora and comprehensive sampling of translocated plant species, we determined whether species translocations were related to species conservation status with binomial generalized linear mixed models with threat status as a binary response variable. Then, we evaluated the taxonomic and phylogenetic biases of translocated plant species relative to national floras based on PD and evolutionary distinctiveness (ED). To evaluate PD and ED, we constructed null models to assess the deviation of observed values from those expected under a scenario in which translocated species were randomly sampled from the species pool of national floras in each country. Although most species lacked conservation status assessment, plant translocations mainly targeted species with high extinction risk at national, European, and global scales. Although plant orders with a higher representativeness of translocated species also tended to have a higher representativeness of native species, the probability of species being translocated varied significantly across plant order, suggesting a significant taxonomic bias. Based on null models and considering all countries, PD and mean ED of translocated plants were higher than expected by chance in most countries. These results suggest that although translocation programs were implemented independently across countries, the diversity of translocated plant species is relevant to conserving PD from national to continental scales and restoring evolutionarily distinct species when these species succeed. We argue that PD indicators should be incorporated into translocation planning to restore target species’ evolutionary trajectories and to contribute to conservation of PD.

Retreat of the Boothia-Lancaster ice stream from its Last Glacial Maximum extent and its role in the origin of Baffin Bay Detrital Carbonate (BBDC) events 0, 1 and 2 - Anne Jennings; Kimberley Jenner; Alexandre Normandeau; Wendy Roth; John Andrews; Robert Kelleher; Juliette Girard; Brendan Reilly; Calvin Campbell; Robbie Bennett (Quaternary Science Reviews, 2025)

Harnessing genotype and phenotype data for population-scale variant classification using large language models and bayesian inference - Toby R. Manders; Christopher A. Tan; Yuya Kobayashi; Alexander Wahl; Carlos Araya; Alexandre Colavin; Flavia M. Facio; Hillery Metz; Jason Reuter; Laure Frésard; Samskruthi R. Padigepati; David A. Stafford; et al. (Human Genetics, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

A global soil spectral grid based on space sensing - José A.M. Demattê; Rodnei Rizzo; Nícolas Augusto Rosin; Raul Roberto Poppiel; Jean Jesus Macedo Novais; Merilyn Taynara Accorsi Amorim; Heidy Soledad Rodriguez-Albarracín; Jorge Tadeu Fim Rosas; Bruno dos Anjos Bartsch; Letícia Guadagnin Vogel; Budiman Minasny; Sabine Grunwald; et al. (Science of The Total Environment, 2025)

Soybean2035: A decadal vision for soybean functional genomics and breeding - Zhixi Tian; Alexandre Lima Nepomuceno; Qingxin Song; Robert M. Stupar; Bin Liu; Fanjiang Kong; Jianxin Ma; Suk-Ha Lee; Scott A. Jackson (Molecular Plant, 2025)

Molecular events accompanying aggregation-induced energy quenching in fucoxanthin-chlorophyll proteins - Maxime T.A. Alexandre; Tjaart P.J. Krüger; Andrew A. Pascal; Vasyl Veremeienko; Manuel J. Llansola-Portoles; Kathi Gundermann; Rienk van Grondelle; Claudia Büchel; Bruno Robert (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2024)

Comparison of α and β-acid isomerization in hops and beer using HPLC, confocal microscopy, spectrofluorimetry and chemical analysis of metabolites and essential oils in flowers of different hop cultivars produced in Brazil - Francisco Mateus Gomes do Nascimento; Maria Teresa Salles Trevisan; Manoel Lourenço Alves Neto; Robert Wyn Owen; Edy Sousa de Brito; Lorena Mara Alexandre e Silva; Késya Amanda Dantas Rocha; Carlos Lenz Cesar; Hernandes Faustino de Carvalho; Vitor Bianchin Pelegati; Sthefanny Alves da Silva; Samuel Pedro Dantas Marques (Food Chemistry, 2024)

Experimental and numerical study of a base-isolated building subjected to vibrations induced by railway traffic - Paulo J. Soares; Robert Arcos; Pedro Alves Costa; Kenny F. Conto; Hassan Liravi; Aires Colaço; Alexandre Castanheira-Pinto; Luís Godinho; Joan Cardona (Engineering Structures, 2024)

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Effectiveness of marine protected areas in safeguarding important migratory megafauna habitat - Xuelei Zhang; Emma L. Carroll; Rochelle Constantine; Virginia Andrews-Goff; Simon Childerhouse; Rosalind Cole; Kimberly T. Goetz; Catherine Meyer; Mike Ogle; Robert Harcourt; Esther Stuck; Alexandre N. Zerbini; et al. (Journal of Environmental Management, 2024)

Wind dispersed tree species have greater maximum height - Ferry Slik; Bruno X. Pinho; Daniel M. Griffith; Edward Webb; Akhilesh Singh Raghubanshi; Adriano C. Quaresma; Aida Cuni Sanchez; Aisha Sultana; Alexandre F. Souza; Andreas Ensslin; Andreas Hemp; Andrew Lowe; et al. (Global Ecology and Biogeography, 2024)
Aim We test the hypothesis that wind dispersal is more common among emergent tree species given that being tall increases the likelihood of effective seed dispersal. Location Americas, Africa and the Asia‐Pacific. Time period 1970–2020. Major taxa studied Gymnosperms and Angiosperms. Methods We used a dataset consisting of tree inventories from 2821 plots across three biogeographic regions (Americas, Africa and Asia‐Pacific), including dry and wet forests, to determine the maximum height and dispersal strategy of 5314 tree species. A web search was used to determine whether species were wind‐dispersed. We compared differences in tree species maximum height between biogeographic regions and examined the relationship between species maximum height and wind dispersal using logistic regression. We also tested whether emergent tree species, that is species with at least one individual taller than the 95% height percentile in one or more plots, were disproportionally wind‐dispersed in dry and wet forests within each biogeographic region. Results Our dataset provides maximum height values for 5314 tree species, of which more than half (2914) had no record of this trait in existing global databases. We found that, on average, tree species in the Americas have lower maximum heights compared to those in Africa and the Asia Pacific. The probability of wind dispersal increased significantly with tree species maximum height and was significantly higher among emergent than non‐emergent tree species in both dry and wet forests in all three biogeographic regions. Main conclusion Wind dispersal is more prevalent in tall, emergent tree species than in non‐emergent species and may thus be an important factor in the evolution of tree species maximum height. By providing the most comprehensive dataset so far of tree species maximum height and wind dispersal strategies, this study paves the way for advancing our understanding of the eco‐evolutionary drivers of tree size.

Variety, growing conditions and processing method act on different structural and biochemical traits to modify viscosity in tomato puree - Miarka Sinkora; Anne-Laure Fanciullino; Nadia Bertin; Robert Giovinazzo; François Zuber; Alexandre Leca; Agnès Rolland-Sabaté; David Page (Food Research International, 2024)

A new exposure protocol adapted for wild bees reveals species-specific impacts of the sulfoximine insecticide sulfoxaflor - Justine Dewaele; Alexandre Barraud; Sara Hellström; Robert J. Paxton; Denis Michez (Ecotoxicology, 2024)
Wild bees are crucial pollinators of flowering plants and concerns are rising about their decline associated with pesticide use. Interspecific variation in wild bee response to pesticide exposure is expected to be related to variation in their morphology, physiology, and ecology, though there are still important knowledge gaps in its understanding. Pesticide risk assessments have largely focussed on the Western honey bee sensitivity considering it protective enough for wild bees. Recently, guidelines for Bombus terrestris and Osmia bicornis testing have been developed but are not yet implemented at a global scale in pesticide risk assessments. Here, we developed and tested a new simplified method of pesticide exposure on wild bee species collected from the field in Belgium. Enough specimens of nine species survived in a laboratory setting and were exposed to oral and topical acute doses of a sulfoximine insecticide. Our results confirm significant variability among wild bee species. We show that Osmia cornuta is more sensitive to sulfoxaflor than B. terrestris , whereas Bombus hypnorum is less sensitive. We propose hypotheses on the mechanisms explaining interspecific variations in sensitivity to pesticides. Future pesticide risk assessments of wild bees will require further refinement of protocols for their controlled housing and exposure.

Scaled mass index derived from aerial photogrammetry associated with predicted metabolic pathway disruptions in free-ranging St. Lawrence Estuary belugas - Meredith Sherrill; Alexandre Bernier-Graveline; Jessica Ewald; Zhiqiang Pang; Michel Moisan; Mathieu Marzelière; Maris Muzzy; Tracy A. Romano; Robert Michaud; Jonathan Verreault (Frontiers in Marine Science, 2024)
The St. Lawrence Estuary (SLE) belugas (Quebec, Canada) are an endangered population whose numbers remain low despite ongoing conservation efforts. Multiple anthropogenic factors and changing environmental conditions are thought to have contributed to the recent 20-year decline in blubber fatty acid concentrations reported in stranded SLE belugas. Despite this evidence that energy reserves within the population are declining, there is currently no method for estimating the body condition of free-ranging animals. The potential metabolic consequences of declining fat reserves have also yet to be explored. The objectives of this study were to use unmanned aerial vehicle (UAV)-based photogrammetry to estimate the scaled mass index (SMI) of free-ranging SLE belugas, and to compare this proxy of body condition to the lipidome of outer-layer blubber samples collected from the same individuals via remote biopsy darting. Morphometric analysis of aerial images ( n = 44 SLE belugas), combined with data collected from animals under professional human care, produced SMI estimates (females: 807 ± 98 kg, males: 743 ± 39 kg) similar in range to those previously calculated for SLE beluga carcasses of known weight. A non-targeted lipidomic analysis followed by pathway enrichment analysis, identified metabolic pathways predicted to show altered activity in association with SMI in the blubber of free-ranging male SLE belugas ( n = 27). Mapping of enriched pathways compared to the Kyoto Encyclopedia of Genes and Genomes (KEGG) metabolic pathways maps, revealed that enriched pathways pertained to the metabolism of multiple lipid classes including fatty acyls and glycerophospholipids. Vitamin A, Vitamin E, and tyrosine metabolism pathways were also enriched in correlation with SMI. This study provides the basis for the development of a non-invasive technique for estimating the body condition of free-ranging SLE belugas and identifies metabolic pathways that merit further exploration to improve our understanding of the potential metabolic impacts of energy loss in cetaceans.

Building references for nature conservation - Alexandre Robert (Conservation Biology, 2024)
Conservation references have long been used in conservation biology to compare current biodiversity processes and states with past conditions. However, beyond the paucity of data for the construction of ancient, even prehuman, references, the relevance of these ancient references for studying ecosystems radically modified by human activities is questionable, particularly when the notions of conservation references and conservation objectives are confused and when several conservation ethics coexist that require distinct references. Because of this implicit heterogeneity in the nature of the references and their temporal baseline, conservation references not only have different meanings, but also deliver different messages. I propose establishing a common framework for conservation references to approach past biological systems and build comparable references between studies and projects. The selection of these references (distinct from conservation objectives) should be an early, explicit, standardized, and transparent milestone in any conservation process and these references should be based on state, pressure, or process dynamics, rather than fixed states. Finally, the importance of the diversity of temporal baselines used to build conservation references and to measure anthropogenic impacts should be recognized to understand the biodiversity crisis in its entirety.

Full-fat corn germ improves the performance and milk fat yield of Girolando cows fed sugarcane bagasse and cactus cladodes as forage sources - Camila S. da Silva; Marco Antônio S. da Gama; Erick Alexandre M. Silva; Emília F. Ribeiro; Silas B. Felix; Carolina C. F. Monteiro; Robert E. Mora-Luna; Júlio Cesar V. de Oliveira; Djalma C. dos Santos; Marcelo A. de Ferreira (Tropical Animal Health and Production, 2024)

Reclassifying historical disasters: From single to multi-hazards - Ryan Lee; Christopher J. White; Mohammed Sarfaraz Gani Adnan; John Douglas; Miguel D. Mahecha; Fiachra E. O'Loughlin; Edoardo Patelli; Alexandre M. Ramos; Matthew J. Roberts; Olivia Martius; Enrico Tubaldi; Bart van den Hurk; et al. (Science of The Total Environment, 2024)

Unidirectional trans‐Atlantic gene flow and a mixed spawning area shape the genetic connectivity of Atlantic bluefin tuna - Natalia Díaz‐Arce; Pierre‐Alexandre Gagnaire; David E. Richardson; John F. Walter; Sophie Arnaud‐Haond; Jean‐Marc Fromentin; Deirdre Brophy; Molly Lutcavage; Piero Addis; Francisco Alemany; Robert Allman; Simeon Deguara; et al. (Molecular Ecology, 2024)
The commercially important Atlantic bluefin tuna ( Thunnus thynnus ), a large migratory fish, has experienced notable recovery aided by accurate resource assessment and effective fisheries management efforts. Traditionally, this species has been perceived as consisting of eastern and western populations, spawning respectively in the Mediterranean Sea and the Gulf of Mexico, with mixing occurring throughout the Atlantic. However, recent studies have challenged this assumption by revealing weak genetic differentiation and identifying a previously unknown spawning ground in the Slope Sea used by Atlantic bluefin tuna of uncertain origin. To further understand the current and past population structure and connectivity of Atlantic bluefin tuna, we have assembled a unique dataset including thousands of genome‐wide single‐nucleotide polymorphisms (SNPs) from 500 larvae, young of the year and spawning adult samples covering the three spawning grounds and including individuals of other Thunnus species. Our analyses support two weakly differentiated but demographically connected ancestral populations that interbreed in the Slope Sea. Moreover, we also identified signatures of introgression from albacore ( Thunnus alalunga ) into the Atlantic bluefin tuna genome, exhibiting varied frequencies across spawning areas, indicating strong gene flow from the Mediterranean Sea towards the Slope Sea. We hypothesize that the observed genetic differentiation may be attributed to increased gene flow caused by a recent intensification of westward migration by the eastern population, which could have implications for the genetic diversity and conservation of western populations. Future conservation efforts should consider these findings to address potential genetic homogenization in the species.

Remote sensing of the Earth's soil color in space and time - Rodnei Rizzo; Alexandre M.J.-C. Wadoux; José A.M. Demattê; Budiman Minasny; Vidal Barrón; Eyal Ben-Dor; Nicolas Francos; Igor Savin; Raul Poppiel; Nelida E.Q. Silvero; Fabrício da Silva Terra; Nícolas Augusto Rosin; et al. (Remote Sensing of Environment, 2023)

Bio-physical determinants of sediment accumulation on an offshore coral reef: A snapshot study - Sterling B. Tebbett; Jodie A. Schlaefer; Casey L. Bowden; William P. Collins; Christopher R. Hemingson; Scott D. Ling; Juliano Morais; Renato A. Morais; Alexandre C. Siqueira; Robert P. Streit; Sam Swan; David R. Bellwood (Science of The Total Environment, 2023)

Efficacy of temporal and spatial abstraction for training accurate machine learning models: A case study in smart thermostats - Karim Boubouh; Robert Basmadjian; Omid Ardakanian; Alexandre Maurer; Rachid Guerraoui (Energy and Buildings, 2023)

Quantifying the effectiveness of shaded fuel breaks from ground-based, aerial, and spaceborne observations - Janine A. Baijnath-Rodino; Alexandre Martinez; Robert A. York; Efi Foufoula-Georgiou; Amir AghaKouchak; Tirtha Banerjee (Forest Ecology and Management, 2023)

Tomato puree quality from field to can: Effects of water and nitrogen-saving strategies - Miarka Sinkora; Anne-Laure Fanciullino; David Page; Robert Giovinazzo; Lucas Lanoë; Alexandre Vilas Boas; Nadia Bertin (European Journal of Agronomy, 2023)

Monitoring time of conservation-driven and mitigation-driven plant translocations in Europe - Margaux Julien; Bertrand Schatz; Alexandre Robert; Bruno Colas (Plant Ecology, 2023)

The IV International Symposium on Fungal Stress and the XIII International Fungal Biology Conference - Alene Alder-Rangel; Alexandre Melo Bailão; Alfredo Herrera-Estrella; Amanda E.A. Rangel; Attila Gácser; Audrey P. Gasch; Claudia B.L. Campos; Christina Peters; Francine Camelim; Fulvia Verde; Geoffrey Michael Gadd; Gerhard Braus; et al. (Fungal Biology, 2023)

Temporo-basal sulcal connections: a manual annotation protocol and an investigation of sexual dimorphism and heritability - Kevin de Matos; Claire Cury; Lydia Chougar; Lachlan T. Strike; Thibault Rolland; Maximilien Riche; Lisa Hemforth; Alexandre Martin; Tobias Banaschewski; Arun L. W. Bokde; Sylvane Desrivières; Herta Flor; et al. (Brain Structure and Function, 2023)

Biomarkers of mitochondrial dysfunction and inflammaging in older adults and blood pressure variability - Leonardo Bencivenga; Mathilde Strumia; Yves Rolland; Laurent Martinez; Philippe Cestac; Sophie Guyonnet; Sandrine Andrieu; Angelo Parini; Alexandre Lucas; Bruno Vellas; Philipe De Souto Barreto; Laure Rouch; et al. (GeroScience, 2023)

Spatial analysis of mercury and stable isotopes in the vulnerable Dusky Grouper Epinephelus marginatus along the Brazilian coast - Mario V. Condini; Christopher R. Malinowski; David J. Hoeinghaus; Brittany L. Harried; Aaron P. Roberts; Brianne K. Soulen; Kathleen J. Roark; Alexis J. Khursigara; Luciano G. Fischer; Bianca Possamai; Maurício Hostim-Silva; Alexandre M. Garcia (Marine Pollution Bulletin, 2023)

Slow and steady wins the race: Diversification rate is independent from body size and lifestyle in Malagasy skinks (Squamata: Scincidae: Scincinae) - Francesco Belluardo; A. Jesus Muñoz-Pajares; Aurélien Miralles; Daniele Silvestro; Walter Cocca; Fanomezana Mihaja Ratsoavina; Andrea Villa; Sam Hyde Roberts; Marcello Mezzasalma; Alexander Zizka; Alexandre Antonelli; Angelica Crottini (Molecular Phylogenetics and Evolution, 2023)

Early Cambrian highly metalliferous black shale in South China: Cu and Zn isotopes and a short review of other non-traditional stable isotopes - Bernd Lehmann; Jan Pašava; Ondřej Šebek; Alexandre Andronikov; Robert Frei; Lingang Xu; Jingwen Mao (Mineralium Deposita, 2022)
Early Cambrian black shales on the Yangtze Platform host a regionally distributed highly metalliferous sulfide-rich carbonaceous unit which has been the subject of extensive debate. This marker unit, with a few centimeters or tens of centimeters in thickness, displays extreme enrichment in Mo and Ni (wt% range), and in a broad spectrum of other metals such as As, Au, PGE, Re, Cu, Zn, Cd, Ag, Sb, Se, Tl, and Hg, and occurs discontinuously along the western passive margin of the Yangtze Platform. It grades laterally in stratigraphically equivalent meter-thick vanadium-rich shale and tens-of-meter-thick sapropelite (combustible shale). New Cu and Zn isotope data, combined with existing Cd, Cr, Ni, Mo, Hg, and Se isotope and other chemical data, allow to attempt an integrated view on the formation of this intriguing unit of hyper-enriched metalliferous black shale. The authigenic Cu enrichment in the 1000-ppm range has produced no or little Cu isotope fractionation (0.03 ± 0.26 ‰ δ 65 Cu) beyond the lithogenic background. Heavy zinc and cadmium isotope enrichment in the sulfidic samples (1.11 ± 0.18 ‰ δ 66 Zn, 0.31 ± 0.10 ‰ δ 114 Cd) is controlled by sulfide fractionation and contrasts with V-rich and barren shale (0.60 ± 0.18 ‰ δ 66 Zn, 0.00 ± 0.14 ‰ δ 114 Cd). The distinctly negative Ni isotope composition of the metalliferous unit (−0.84 ± 0.05 ‰ δ 60 Ni) with Ni in the percent range has been interpreted as due to hydrothermal activity related to the leaching of mafic rocks and their sulfides. Sorption processes (Fe-oxyhydroxides) and redox cycling in the water column and the bottom sediment with microbial activity could be an alternative interpretation. The extreme metal enrichment can be understood as due to a process chain, from high biological productivity in the oxic photic zone to sulfate reduction in the deeper sulfidic water column and upper sediment layer. Key to the metal enrichment seems to be extremely low clastic sedimentation and advanced carbon destruction by anaerobic oxidation. Hydrothermal input of basinal brines along the rifted margin of the Yangtze Platform was likely a part of this scenario.

Toward a decade of ocean science for sustainable development through acoustic animal tracking - Josep Alós; Kim Aarestrup; David Abecasis; Pedro Afonso; Alexandre Alonso‐Fernandez; Eneko Aspillaga; Margarida Barcelo‐Serra; Jonathan Bolland; Miguel Cabanellas‐Reboredo; Robert Lennox; Ross McGill; Aytaç Özgül; et al. (Global Change Biology, 2022)
The ocean is a key component of the Earth's dynamics, providing a great variety of ecosystem services to humans. Yet, human activities are globally changing its structure and major components, including marine biodiversity. In this context, the United Nations has proclaimed a Decade of Ocean Science for Sustainable Development to tackle the scientific challenges necessary for a sustainable use of the ocean by means of the Sustainable Development Goal 14 (SDG14). Here, we review how Acoustic animal Tracking, a widely distributed methodology of tracking marine biodiversity with electronic devices, can provide a roadmap for implementing the major Actions to achieve the SDG14. We show that acoustic tracking can be used to reduce and monitor the effects of marine pollution including noise, light, and plastic pollution. Acoustic tracking can be effectively used to monitor the responses of marine biodiversity to human‐made infrastructures and habitat restoration, as well as to determine the effects of hypoxia, ocean warming, and acidification. Acoustic tracking has been historically used to inform fisheries management, the design of marine protected areas, and the detection of essential habitats, rendering this technique particularly attractive to achieve the sustainable fishing and spatial protection target goals of the SDG14. Finally, acoustic tracking can contribute to end illegal, unreported, and unregulated fishing by providing tools to monitor marine biodiversity against poachers and promote the development of Small Islands Developing States and developing countries. To fully benefit from acoustic tracking supporting the SDG14 Targets, trans‐boundary collaborative efforts through tracking networks are required to promote ocean information sharing and ocean literacy. We therefore propose acoustic tracking and tracking networks as relevant contributors to tackle the scientific challenges that are necessary for a sustainable use of the ocean promoted by the United Nations.

AMAZONIA CAMTRAP: A data set of mammal, bird, and reptile species recorded with camera traps in the Amazon forest - Ana Carolina Antunes; Anelise Montanarin; Diogo Maia Gräbin; Erison Carlos dos Santos Monteiro; Fernando Ferreira de Pinho; Guilherme Costa Alvarenga; Jorge Ahumada; Robert B. Wallace; Emiliano Esterci Ramalho; Adrian Paul Ashton Barnett; Alex Bager; Alexandre Martins Costa Lopes; et al. (Ecology, 2022)
The Amazon forest has the highest biodiversity on Earth. However, information on Amazonian vertebrate diversity is still deficient and scattered across the published, peer‐reviewed, and gray literature and in unpublished raw data. Camera traps are an effective non‐invasive method of surveying vertebrates, applicable to different scales of time and space. In this study, we organized and standardized camera trap records from different Amazon regions to compile the most extensive data set of inventories of mammal, bird, and reptile species ever assembled for the area. The complete data set comprises 154,123 records of 317 species (185 birds, 119 mammals, and 13 reptiles) gathered from surveys from the Amazonian portion of eight countries (Brazil, Bolivia, Colombia, Ecuador, French Guiana, Peru, Suriname, and Venezuela). The most frequently recorded species per taxa were: mammals: Cuniculus paca (11,907 records); birds: Pauxi tuberosa (3713 records); and reptiles: Tupinambis teguixin (716 records). The information detailed in this data paper opens up opportunities for new ecological studies at different spatial and temporal scales, allowing for a more accurate evaluation of the effects of habitat loss, fragmentation, climate change, and other human‐mediated defaunation processes in one of the most important and threatened tropical environments in the world. The data set is not copyright restricted; please cite this data paper when using its data in publications and we also request that researchers and educators inform us of how they are using these data.

New Zealand southern right whale (Eubalaena australis; Tohorā nō Aotearoa) behavioural phenology, demographic composition, and habitat use in Port Ross, Auckland Islands over three decades: 1998–2021 - Emma L. Carroll; Leena Riekkola; Virginia Andrews-Goff; C. Scott Baker; Rochelle Constantine; Ros Cole; Kim Goetz; Robert Harcourt; David Lundquist; Catherine Meyer; Mike Ogle; Richard O’Rorke; et al. (Polar Biology, 2022)
Changes in habitat availability and prey abundance are predicted to adversely influence survival and reproduction of wildlife in the Southern Ocean. Some populations of southern right whale (SRW; Eubalaena australis ) are showing dramatic changes in habitat use. Surveys were undertaken in the austral winters of 2020 and 2021 at the key nursery and socialising ground for New Zealand SRWs: Port Ross, Auckland Islands, with 548 encounters and 599 skin biopsy samples collected. Data from these two surveys spanned peak periods of use and were used to test the hypothesis there have been shifts in the phenology, demographic composition and behaviour of SRWs using the Auckland Islands over the past three decades. The behavioural phenology and demographic composition of SRW resembles that observed in the 1990s. In contrast, the proportion of groups containing cow-calf pairs increased from 20% in the 1998 survey to 50% in 2020/21. These changes are consistent with a growing population undergoing strong recruitment, not limited by food resources. Continued use of Port Ross by all SRW demographic classes confirms this as key habitat for SRW in New Zealand waters, and we support increased enforcement of existing management measures to reduce whale-vessel interactions in this remote subantarctic archipelago.

Low survival of eggs and nestlings explain the decline of a local Jankowski’s Bunting population - Zheng Han; Alexandre Robert; Haitao Wang; Frédéric Jiguet (Journal of Ornithology, 2022)

Utilizing Marine Cultural Heritage for the Preservation of Coastal Systems in East Africa - Georgia Holly; Arturo Rey da Silva; Jon Henderson; Caesar Bita; Wes Forsythe; Zacarias Alexandre Ombe; Christopher Poonian; Hayley Roberts (Journal of Marine Science and Engineering, 2022)
This paper presents the key contributions of marine cultural heritage to the survival of coastal ecosystems and the communities that rely on them in East Africa. Marine cultural heritage (MCH) describes the evidence of past human interactions with coastal and marine space, encompassing tangible material culture remains and associated intangible cultural expressions within coastal communities. By incorporating the protection of MCH into local and regional environmental frameworks, we gain an essential indicator to monitor change dynamics in natural habitats, the cumulative impacts of climate change, and the development of social adaptation strategies. An essential aspect of this development is the move away from global sustainability strategies towards community-centric management and stewardship. Such processes utilise a combination of traditional knowledge systems and scientific approaches designed to harness targeted economic, ecological, and social sustainable development. To argue for the incorporation of MCH into local and regional environmental frameworks in the area, this paper presents four case studies from the Rising from the Depths Network, a challenge-led research network focusing on harnessing the potential of MCH to bring sustainable development strategies to East Africa.

Cover Image: Volume 25 Number 3, March 2022 - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)

AVONET: morphological, ecological and geographical data for all birds - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.

Disturbance‐induced emigration: an overlooked mechanism that reduces metapopulation extinction risk - Alexandre Mestre; Michael Barfield; James H. Peniston; Pedro R. Peres‐Neto; Francesc Mesquita‐Joanes; Robert D. Holt (Ecology, 2021)
Emigration propensity (i.e., the tendency to leave undisturbed patches) is a key life‐history trait of organisms in metapopulations with local extinctions and colonizations. Metapopulation models of dispersal evolution typically assume that patch disturbance kills all individuals within the patch, thus causing local extinction. However, individuals may instead be able to leave a patch when it is disturbed, either by fleeing before being killed or simply because the disturbance destroys the patch without causing mortality. This scenario may pertain to a wide range of organisms from horizontally transmitted symbionts, to aquatic insects inhabiting temporary ponds, to vertebrates living in fragmented forests. We generalized a Levins‐type metapopulation model of dispersal evolution by adding a new parameter of disturbance escape probability, which incorporates a second source of dispersal into the model: disturbance‐induced emigration. We show that disturbance escape expands the domain of metapopulation viability and selects for lower rates of emigration propensity when disturbance rates are high. The fitness gains from disturbance‐induced emigration are generally moderate, suggesting that disturbance escape might act more as a complementary dispersal strategy rather than a replacement to emigration propensity, at least for metapopulations that meet the assumptions of the Levins‐type model. Yet disturbance‐induced emigration may in some circumstances rescue a metapopulation from long‐term extinction when the combination of high disturbance rates and low local population growth rates compromises its viability. Further, a metapopulation could persist exclusively by disturbance escape if local carrying capacities are large enough to counterbalance two sources of mortality: mortality driven by disturbance and mortality during dispersal. This study opens two promising research lines: (1) the investigation of disturbance escape in metapopulations of ephemeral habitats with unsaturated populations and non‐equilibrium dynamics and (2) the incorporation of information costs to investigate the joint evolution of disturbance escape and emigration propensity.

Oldowan stone knapping and percussive activities on a raw material reservoir deposit 1.4 million years ago at Barranco León (Orce, Spain) - Stefania Titton; Oriol Oms; Deborah Barsky; Amèlia Bargalló; Alexia Serrano-Ramos; José García-Solano; Christian Sánchez-Bandera; José Yravedra; Hugues-Alexandre Blain; Isidro Toro-Moyano; Juan Manuel Jiménez Arenas; Robert Sala-Ramos (Archaeological and Anthropological Sciences, 2021)

Dynamics of marine predators off an oceanic island and implications for management of a preventative shark fishing program - Yuri Niella; Alexandre Wiefels; Ulian Almeida; Sébastien Jaquemet; Erwann Lagabrielle; Robert Harcourt; Victor Peddemors; David Guyomard (Marine Biology, 2021)

Glenn R. VanBlaricom † 1949–2020 - Alexandre N. Zerbini; Anthony J. Orr; Amanda L. Bradford; Michael Kenner; Robert Suydam; Carlos Alvarez‐Flores; Leah R. Gerber; Kristin Laidre; Donna Hauser; Laura Hoberecht (Marine Mammal Science, 2021)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Long lasting breeding performance differences between wild-born and released females in a reinforced North African Houbara bustard (Chlamydotis undulata undulata) population: a matter of release strategy - Léo Bacon; Alexandre Robert; Yves Hingrat (Biodiversity and Conservation, 2019)

Within- and between-year variations of reproductive strategy and cost in a population of Siberian chipmunks - Christie Le Coeur; Benoît Pisanu; Jean-Louis Chapuis; Alexandre Robert (Oecologia, 2018)

Vascular plant‐mediated controls on atmospheric carbon assimilation and peat carbon decomposition under climate change - Konstantin Gavazov; Remy Albrecht; Alexandre Buttler; Ellen Dorrepaal; Mark H. Garnett; Sebastien Gogo; Frank Hagedorn; Robert T. E. Mills; Bjorn J. M. Robroek; Luca Bragazza (Global Change Biology, 2018)
Climate change can alter peatland plant community composition by promoting the growth of vascular plants. How such vegetation change affects peatland carbon dynamics remains, however, unclear. In order to assess the effect of vegetation change on carbon uptake and release, we performed a vascular plant‐removal experiment in two Sphagnum ‐dominated peatlands that represent contrasting stages of natural vegetation succession along a climatic gradient. Periodic measurements of net ecosystem CO 2 exchange revealed that vascular plants play a crucial role in assuring the potential for net carbon uptake, particularly with a warmer climate. The presence of vascular plants, however, also increased ecosystem respiration, and by using the seasonal variation of respired CO 2 radiocarbon (bomb‐ 14 C) signature we demonstrate an enhanced heterotrophic decomposition of peat carbon due to rhizosphere priming. The observed rhizosphere priming of peat carbon decomposition was matched by more advanced humification of dissolved organic matter, which remained apparent beyond the plant growing season. Our results underline the relevance of rhizosphere priming in peatlands, especially when assessing the future carbon sink function of peatlands undergoing a shift in vegetation community composition in association with climate change.

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Occurrence of multi-class surfactants in urban wastewater: contribution of a healthcare facility to the pollution transported into the sewerage system - Alexandre Bergé; Laure Wiest; Robert Baudot; Barbara Giroud; Emmanuelle Vulliet (Environmental Science and Pollution Research, 2018)

Two-year survey of specific hospital wastewater treatment and its impact on pharmaceutical discharges - Laure Wiest; Teofana Chonova; Alexandre Bergé; Robert Baudot; Frédérique Bessueille-Barbier; Linda Ayouni-Derouiche; Emmanuelle Vulliet (Environmental Science and Pollution Research, 2018)

Toxicity of TiO2 nanoparticles on the NRK52E renal cell line - Xavier Valentini; Lara Absil; Guy Laurent; Alexandre Robbe; Sophie Laurent; Robert Muller; Alexandre Legrand; Denis Nonclercq (Molecular & Cellular Toxicology, 2017)

Fixism and conservation science - Alexandre Robert; Colin Fontaine; Simon Veron; Anne‐Christine Monnet; Marine Legrand; Joanne Clavel; Stéphane Chantepie; Denis Couvet; Frédéric Ducarme; Benoît Fontaine; Frédéric Jiguet; Isabelle le Viol; et al. (Conservation Biology, 2017)
The field of biodiversity conservation has recently been criticized as relying on a fixist view of the living world in which existing species constitute at the same time targets of conservation efforts and static states of reference, which is in apparent disagreement with evolutionary dynamics. We reviewed the prominent role of species as conservation units and the common benchmark approach to conservation that aims to use past biodiversity as a reference to conserve current biodiversity. We found that the species approach is justified by the discrepancy between the time scales of macroevolution and human influence and that biodiversity benchmarks are based on reference processes rather than fixed reference states. Overall, we argue that the ethical and theoretical frameworks underlying conservation research are based on macroevolutionary processes, such as extinction dynamics. Current species, phylogenetic, community, and functional conservation approaches constitute short‐term responses to short‐term human effects on these reference processes, and these approaches are consistent with evolutionary principles.

Habitat requirements and conservation needs of peripheral populations: the case of the great crested newt (Triturus cristatus) in the Scottish Highlands - Alexandre Miró; David O’Brien; Jeanette Hall; Robert Jehle (Hydrobiologia, 2017)

A multicenter assessment of single-cell models aligned to standard measures of cell health for prediction of acute hepatotoxicity - Rowena L. Sison-Young; Volker M. Lauschke; Esther Johann; Eliane Alexandre; Sébastien Antherieu; Hélène Aerts; Helga H. J. Gerets; Gilles Labbe; Delphine Hoët; Martina Dorau; Christopher A. Schofield; Cerys A. Lovatt; et al. (Archives of Toxicology, 2017)

Contrasting patterns of genetic diversity and spatial structure in an invasive symbiont-host association - Alexandre Mestre; Roger K. Butlin; William E. Kelso; Robert Romaire; Christopher P. Bonvillain; Juan S. Monrós; Francesc Mesquita-Joanes (Biological Invasions, 2016)

Inter-annual and inter-individual variations in survival exhibit strong seasonality in a hibernating rodent - Christie Le Cœur; Stéphane Chantepie; Benoît Pisanu; Jean-Louis Chapuis; Alexandre Robert (Oecologia, 2016)

Succession of Permian and Mesozoic metasomatic events in the eastern Pyrenees with emphasis on the Trimouns talc–chlorite deposit - Alexandre Boutin; Michel de Saint Blanquat; Marc Poujol; Philippe Boulvais; Philippe de Parseval; Caroline Rouleau; Jean-François Robert (International Journal of Earth Sciences, 2016)

A therapeutic challenge: catastrophic anti-phospholipid syndrome with diffuse alveolar haemorrhage - Nihal Martis; Eléa Blanchouin; Rémi Lazdunski; Sarah Lechtman; Alexandre Robert; Hervé Hyvernat; Denis Doyen; Jean Dellamonica; Gilles Bernardin (Immunologic Research, 2015)

Biodiversity trends are as bad as expected - Anne Teyssèdre; Alexandre Robert (Biodiversity and Conservation, 2015)

Effects of enamel matrix genes on dental caries are moderated by fluoride exposures - John R. Shaffer; Jenna C. Carlson; Brooklyn O. C. Stanley; Eleanor Feingold; Margaret Cooper; Michael M. Vanyukov; Brion S. Maher; Rebecca L. Slayton; Marcia C. Willing; Steven E. Reis; Daniel W. McNeil; Richard J. Crout; et al. (Human Genetics, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Biotic and Abiotic Constraints on the Decomposition of Fagus sylvatica Leaf Litter Along an Altitudinal Gradient in Contrasting Land-Use Types - Konstantin Gavazov; Robert Mills; Thomas Spiegelberger; Jonathan Lenglet; Alexandre Buttler (Ecosystems, 2014)

Probing the carotenoid content of intact Cyclotella cells by resonance Raman spectroscopy - Maxime T. A. Alexandre; Kathi Gundermann; Andrew A. Pascal; Rienk van Grondelle; Claudia Büchel; Bruno Robert (Photosynthesis Research, 2014)

Poor fen succession over ombrotrophic peat related to late Holocene increased surface wetness in subarctic Quebec, Canada - SIMON VAN BELLEN; MICHELLE GARNEAU; ADAM A. ALI; ALEXANDRE LAMARRE; ÉLISABETH C. ROBERT; GABRIEL MAGNAN; HANS ASNONG; STEVE PRATTE (Journal of Quaternary Science, 2013)
Northern peatlands act as archives of environmental change through their sensitivity to water balance fluctuations, while being significant contributors to global greenhouse gas dynamics. Subarctic fens in north‐eastern Canada are characterized by a dominance of pools and flarks. We aimed to reconstruct the late Holocene hydrological conditions of these fens to establish the timing of the initiation of pool and flark formation and possible links with climate. Testate amoebae and plant macrofossils from five cores, sampled in three fens, were analysed to infer water tables with chronologies based on 14 C and 210 Pb dating. All sites showed the presence of relatively dry, ombrotrophic conditions with abundant Picea from 5000 cal a BP, followed by a first shift to wet, poor fen conditions with pool and flark development around 3000 cal a BP and a subsequent wet shift after ∼800 cal a BP. These trends coincide with previously observed Neoglacial and Little Ice Age cooler and wetter conditions and therefore climate may well have been a dominant factor in the initiation and development of pools and flarks over the late Holocene. The effect of anticipated climate change on subarctic peatlands remains unclear, although wetter conditions might enhance pool expansion to the detriment of terrestrial components.

Are urban green spaces suitable for woodland carabids? First insights from a short-term experiment - Alan Vergnes; Stéphane Chantepie; Alexandre Robert; Philippe Clergeau (Journal of Insect Conservation, 2013)

Paths to selection on life history loci in different natural environments across the native range of A rabidopsis thaliana - Alexandre Fournier‐Level; Amity M. Wilczek; Martha D. Cooper; Judith L. Roe; Jillian Anderson; Deren Eaton; Brook T. Moyers; Renee H. Petipas; Robert N. Schaeffer; Bjorn Pieper; Matthieu Reymond; Maarten Koornneef; et al. (Molecular Ecology, 2013)
Selection on quantitative trait loci ( QTL ) may vary among natural environments due to differences in the genetic architecture of traits, environment‐specific allelic effects or changes in the direction and magnitude of selection on specific traits. To dissect the environmental differences in selection on life history QTL across climatic regions, we grew a panel of interconnected recombinant inbred lines ( RIL s) of Arabidopsis thaliana in four field sites across its native European range. For each environment, we mapped QTL for growth, reproductive timing and development. Several QTL were pleiotropic across environments, three colocalizing with known functional polymorphisms in flowering time genes ( CRY 2 , FRI and MAF 2‐5 ), but major QTL differed across field sites, showing conditional neutrality. We used structural equation models to trace selection paths from QTL to lifetime fitness in each environment. Only three QTL directly affected fruit number, measuring fitness. Most QTL had an indirect effect on fitness through their effect on bolting time or leaf length. Influence of life history traits on fitness differed dramatically across sites, resulting in different patterns of selection on reproductive timing and underlying QTL . In two oceanic field sites with high prereproductive mortality, QTL alleles contributing to early reproduction resulted in greater fruit production, conferring selective advantage, whereas alleles contributing to later reproduction resulted in larger size and higher fitness in a continental site. This demonstrates how environmental variation leads to change in both QTL effect sizes and direction of selection on traits, justifying the persistence of allelic polymorphism at life history QTL across the species range.

Temporal peaks in social information: prospectors investigate conspecific nests after a simulated predator visit - Robert L. Thomson; Päivi M. Sirkiä; Alexandre Villers; Toni Laaksonen (Behavioral Ecology and Sociobiology, 2013)

Erratum to: Properties of spatial channels underlying the detection of orientation-modulations - Alexandre Reynaud; Robert F. Hess (Experimental Brain Research, 2012)

The interaction between reproductive cost and individual quality is mediated by oceanic conditions in a long‐lived bird - Alexandre Robert; Vítor H. Paiva; Mark Bolton; Frédéric Jiguet; Joël Bried (Ecology, 2012)
Environmental variability, costs of reproduction, and heterogeneity in individual quality are three important sources of the temporal and interindividual variations in vital rates of wild populations. Based on an 18‐year monitoring of an endangered, recently described, long‐lived seabird, Monteiro's Storm‐Petrel ( Oceanodroma monteiroi ), we designed multistate survival models to separate the effects of the reproductive cost (breeders vs. nonbreeders) and individual quality (successful vs. unsuccessful breeders) in relation to temporally variable demographic and oceanographic properties. The analysis revealed a gradient of individual quality from nonbreeders, to unsuccessful breeders, to successful breeders. The survival rates of unsuccessful breeders (0.90 ± 0.023, mean ± SE) tended to decrease in years of high average breeding success and were more sensitive to oceanographic variation than those of both (high‐quality) successful breeders (0.97 ± 0.015) and (low‐quality) nonbreeders (0.83 ± 0.028). Overall, our results indicate that reproductive costs act on individuals of intermediate quality and are mediated by environmental harshness.

Properties of spatial channels underlying the detection of orientation-modulations - Alexandre Reynaud; Robert F. Hess (Experimental Brain Research, 2012)

Host and habitat specialization of avian malaria in Africa - CLAIRE LOISEAU; RYAN J. HARRIGAN; ALEXANDRE ROBERT; RAURI C. K. BOWIE; HENRI A. THOMASSEN; THOMAS B. SMITH; RAVINDER N. M. SEHGAL (Molecular Ecology, 2012)
Studies of both vertebrates and invertebrates have suggested that specialists, as compared to generalists, are likely to suffer more serious declines in response to environmental change. Less is known about the effects of environmental conditions on specialist versus generalist parasites. Here, we study the evolutionary strategies of malaria parasites ( Plasmodium spp.) among different bird host communities. We determined the parasite diversity and prevalence of avian malaria in three bird communities in the lowland forests in Cameroon, highland forests in East Africa and fynbos in South Africa. We calculated the host specificity index of parasites to examine the range of hosts parasitized as a function of the habitat and investigated the phylogenetic relationships of parasites. First, using phylogenetic and ancestral reconstruction analyses, we found an evolutionary tendency for generalist malaria parasites to become specialists. The transition rate at which generalists become specialists was nearly four times as great as the rate at which specialists become generalists. We also found more specialist parasites and greater parasite diversity in African lowland rainforests as compared to the more climatically variable habitats of the fynbos and the highland forests. Thus, with environmental changes, we anticipate a change in the distribution of both specialist and generalist parasites with potential impacts on bird communities.

The response of the human circulatory system to an acute 200-μT, 60-Hz magnetic field exposure - David A. McNamee; Michael Corbacio; Julie K. Weller; Samantha Brown; Robert Z. Stodilka; Frank S. Prato; Yves Bureau; Alex W. Thomas; Alexandre G. Legros (International Archives of Occupational and Environmental Health, 2011)

The transcription factor GATA-2 does not associate with angiographic coronary artery disease in the Ottawa Heart Genomics and Cleveland Clinic GeneBank Studies - Sonny Dandona; Li Chen; Meng Fan; Md Afaque Alam; Olivia Assogba; Melanie Belanger; Kathryn Williams; George A. Wells; W. H. Wilson Tang; Stephen G. Ellis; Stanley L. Hazen; Ruth McPherson; et al. (Human Genetics, 2010)

Recovery dynamics and viability of the white-tailed eagle (Haliaeetus albicilla) in Germany - Justine Sulawa; Alexandre Robert; Ulrich Köppen; Peter Hauff; Oliver Krone (Biodiversity and Conservation, 2010)

Identification of susceptibility genes for complex diseases using pooling-based genome-wide association scans - Yohan Bossé; François Bacot; Alexandre Montpetit; Johan Rung; Hui-Qi Qu; James C. Engert; Constantin Polychronakos; Thomas J. Hudson; Philippe Froguel; Robert Sladek; Martin Desrosiers (Human Genetics, 2009)

Releasing Adults versus Young in Reintroductions: Interactions between Demography and Genetics - ALEXANDRE ROBERT; FRANÇOIS SARRAZIN; DENIS COUVET; STÉPHANE LEGENDRE (Conservation Biology, 2004)
We integrated genetics and demography into population modeling in the context of species restorations, in which both the origin of released individuals and the management strategy may influence the success of introduction. Through an explicit individual‐based simulation approach, we investigated the effects of the age of released individuals by exploring the relative merits of releasing juveniles or adults to establish populations. We included the effect of genetic variability responsible for inbreeding depression and mutational meltdown. Our general analysis uncovered an interaction between the age of founders and the extent of intrapopulation fitness variability, which substantially influenced the efficiency of selection in populations founded by juveniles and had subsequent positive consequences for long‐term persistence compared with the case in which adults were released. We then applied the model to the case of the reintroduction of the Griffon Vulture ( Gyps fulvus fulvus ) to southern France, for which post‐release data were available. The demographic aspects of this reintroduction were already analyzed and published, suggesting that it is more efficient to release adults than juveniles, despite an observed reduction of demographic parameters following the release of adults. In that context, the inclusion of genetic considerations qualitatively changes the conclusion, predicting reduced long‐term extinction risk if juveniles rather than adults are released.

Influence of the rate of introduction on the fitness of restored populations - Alexandre Robert; Franois Sarrazin Denis Couvet (Conservation Genetics, 2004)

Variation among Individuals, Demographic Stochasticity, and Extinction: Response to Kendall and Fox - Alexandre Robert; François Sarrazin; Denis Couvet (Conservation Biology, 2003)

Bottlenecks in large populations: the effect of immigration on population viability - Alexandre Robert; Denis Couvet; François Sarrazin (Evolutionary Ecology, 2003)

Interspecific Variation in Terpenoid Composition of Defensive Secretions of European Reticulitermes Termites - Alexandre Quintana; Judith Reinhard; Robert Faure; Paolo Uva; Anne-Geneviève Bagnères; Georges Massiot; Jean-Luc Clément (Journal of Chemical Ecology, 2003)

The establishment of a network of European human research tissue banks - Samantha Orr; Eliane Alexandre; Brain Clark; Robert Combes; Lueder M. Fels; Neil Gray; Ann-Cathrine Jönsson-Rylander; Heikki Helin; Jukka Koistinen; Teija Oinonen; Lysiane Richert; Rivka Ravid; et al. (Cell and Tissue Banking, 2002)

The murine orthologue of the Golgi-localized TPTE protein provides clues to the evolutionary history of the human TPTE gene family - Michel Guipponi; Caroline Tapparel; Olivier Jousson; Nathalie Scamuffa; Christophe Mas; Colette Rossier; Pierre Hutter; Paolo Meda; Robert Lyle; Alexandre Reymond; Stylianos E. Antonarakis (Human Genetics, 2001)